Knockdown of Thymidine Kinase 1 Suppresses Cell Proliferation, Invasion, Migration, and Epithelial–Mesenchymal Transition in Thyroid Carcinoma Cells - Liu, Chang; Wang, Jian; Zhao, Li; He, Hui; Zhao, Pan; Peng, Zheng; Liu, Feiyuan; Chen, Juan; Wu, Weiqing; Wang, Guangsuo; Dong, Fajin (Frontiers in Oncology, 2020)
Patients with advanced thyroid carcinoma had poor prognosis with low overall survival. Unfortunately, the underlying mechanisms of thyroid carcinoma progression remain unclear. The elevated expression of thymidine kinase 1 (TK1) has been implicated in the progression of thyroid carcinoma, while the role of TK1 in thyroid carcinoma progression has not been explored. The present study aimed to determine the role TK1 in the progression of thyroid cancer and to explore the underlying molecular mechanisms. In this study, it was found that serum TK1 levels were markedly increased in the patients with thyroid nodules. Further online data mining showed that TK1 expression was up-regulated in thyroid carcinoma tissues and higher expression of TK1 was correlated with shorter disease free survival of patients with thyroid carcinoma. Silencing of TK1 suppressed cell proliferation, invasion, migration and epithelial-mesenchymal transition, and also induced cell apoptosis in the thyroid carcinoma cell lines. Animal studies showed that TK1 knockdown inhibited in vivo tumor growth of thyroid carcinoma cells. Importantly, miR-34a-5p was found to be down-regulated in the thyroid carcinoma cells. Furthermore, miR-34a-5p targeted the 3’ untranslated region of TK1 and suppressed the expression of TK1 in thyroid carcinoma cell lines. In summary, firstly, these results demonstrated the up-regulation of TK1 in thyroid nodules and thyroid carcinoma tissues; secondly, TK1 promoted thyroid carcinoma cell proliferation, invasion and migration; lastly, TK1 was negatively regulated by miR-34a-5p. Our study may provide novel insights into the role of TK1 in regulating thyroid carcinoma progression.